(untitled) (International relations and international law Journal, 2021)
Central Asia is recognized as the heart of the Eurasian continent, and is considered as a geopolitical region in the eyes of power countries. After collapse of Soviet Union, and independence of Central Asian countries, the interest and attention of the leading countries in world politics to these countries has grown rapidly. In 2013, China has launched the Belt and Road Initiative (BRI) economical strategy amongst all the countries. However, as a major political power in the region, Russia’s interests in the region are paramount, and Russian and Chinese studies have suggested that the initiative is in Russia’s interests. In 2015, Russia and Kazakhstan and Kyrgyzstan have implemented a customs agreement on the basis of the Eurasian Economic Union. That same year, China announced to the world that it had established cooperation with the Belt and Road Initiative and the Eurasian Economic Union. It is obvious that the cooperation between the two sides will have a positive impact on the development of the economy and industry in the region. This article examines the relationship between the Eurasian Economic Union and the Belt and Road Initiative in mathematical theory and examines the relationship between the two unions in terms of common interests and some conflicts. Key words: EAEU, One Belt One Road, Central Asia, Silk Road, Regional Economic Cooperation.